Perhitungan Cadangan Dan Stripping Ratio Dengan Menggunakan Software Surpac 6.3 Pada Pit Padawa-1 Di Pt. Pam Mineral Tbk Desa Laroenae Kecamatan Bungku Pesisir Kabupaten Morowali Provinsi Sulawesi Tengah - Litho Aron Palangga; Hasni Kasim; Hendra Sani (Journal Teknik Dan Teknologi, 2025)
PT. PAM Mineral Tbk is one of the companies with Production Operation Mining Business License Area (IUP-OP) with an area of 106 Ha. To carry out the mining process, mine planning is first carried out so that it can be considered with the existing capacity and avoid losses until the mining process takes place. Due to the nature of the relatively uneven distribution of ore content. One of them is making a pit design as a reference and guide before the mining process occurs. In designing a mining pit, it is intended to calculate the volume of reserves, Over Burden, and stripping ratio , so that a mining pit can be designed that takes into account aspects of quality, capacity, economy, environment and safety factors